Effects of Acute Alcohol Intoxication on Empathic Neural Responses for Pain - Hu, Yang; Cui, Zhuoya; Fan, Mingxia; Pei, Yilai; Wang, Zhaoxin (Frontiers in Human Neuroscience, 2018)
The questions whether and how empathy for pain can be modulated by acute alcohol intoxication in the non-dependent population remain unanswered. To address these questions, a double-blind, placebo-controlled, within-subject study design was adopted in this study, in which healthy social drinkers were asked to complete a pain-judgment task using pictures depicting others’ body parts in painful or non-painful situations during fMRI scanning, either under the influence of alcohol intoxication or placebo conditions. Empathic neural activity for pain was reduced by alcohol intoxication only in the dorsal anterior cingulate cortex (dACC). More interestingly, we observed that empathic neural activity for pain in the right anterior insula (rAI) was significantly correlated with trait empathy only after alcohol intoxication, along with impaired functional connectivity between the rAI and the fronto-parietal attention network. Our results reveal that alcohol intoxication not only inhibited empathic neural responses for pain but also led to trait empathy inflation, possibly via impaired top-down attentional control. These findings help to explain the neural mechanism underlying alcohol-related social problems.